Effect of Carbon Fillers on Mechanical Properties of Heat-Treated Needle-Punched Nonwoven Preforms. Issue 2 (22nd January 2017) - Dhanakodi, A. K. P.; Giri Dev, V. R.
ABSTRACT: In this study, nonwovens comprising of flax and polypropylene were prepared by needle punching nonwoven process. Carbon black was added as filler in varying proportions 1, 3, and 5% to the needle-punched nonwovens. These samples were heatset at 160, 170, and 180°C and the tensile properties of the nonwovens were studied. The tensile and thermal properties of the nonwovens were studied by universal testing machines and thermogravimetric analyzer. The addition of carbon black led to the 313% increase in strength compared to the control sample. The addition of carbon black to the nonwoven would pave the way for achieving improved mechanical properties if it is used as a precursor for preparing thermoplastic composites. GRAPHICAL ABSTRACT: